2019
DOI: 10.1016/j.jpainsymman.2018.12.327
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy for Trousseau Syndrome in a Terminally Ill Cancer Patient

Abstract: Trousseau syndrome was first described by Armand Trousseau in 1865 and is characterized by hypercoagulation resulting from malignant tumors. This complication can markedly impact quality of life (QOL). This is the first report of a terminally ill patient who developed large-vessel occlusion stroke from Trousseau syndrome and underwent mechanical thrombectomy. A 75-year-old woman presented with Stage IV ovarian cancer. Goals of care were transitioned to palliative care. The patient was hospitalized with vertebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…This is because the onset of stroke is considered to affect the overall mortality in patients with malignancy due to the contribution of various factors including termination of malignancy treatment and worsening of general condition (immune system, nutrient state, and frailty). However, our results showed that even with the poor long-term prognosis, EVT could at least recover performance status and enable improved quality of life in some patients ( 14 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This is because the onset of stroke is considered to affect the overall mortality in patients with malignancy due to the contribution of various factors including termination of malignancy treatment and worsening of general condition (immune system, nutrient state, and frailty). However, our results showed that even with the poor long-term prognosis, EVT could at least recover performance status and enable improved quality of life in some patients ( 14 ).…”
Section: Discussionmentioning
confidence: 75%
“…Prestroke mRS score was 0 for nine patients, 2 for one patient, and 3 for two patients. NIHSS score at admission was 17.2 [interquartile range (IQR), [14][15][16][17][18][19][20][21] and ASPECTS ranged from 8 to 10. The location of atrial occlusions was determined at the internal cerebral artery (ICA) (n = 2), proximal portion of the middle cerebral artery (MCA) (M1; n = 8), and middle portion of the MCA (M2; n = 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first report of dual endovascular intervention in a CCI patient with Trousseau syndrome. Endovascular therapy for cerebral infarction in Trousseau syndrome is rarely reported (24). All of these previous cases exhibited terminal stage of cancer, elevated D-dimer, and thrombus with white coloration consisting of fibrin and platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Trousseau syndrome is a condition characterized as hypercoagulation disorder related to malignancy (1). It is considered a common cause of ischemic stroke in terminally ill patients, and several affected patients have been reported to undergo mechanical thrombectomy (24). Here, we report a rare case of synchronous cardiocerebral infarction (CCI) caused by Trousseau syndrome in a patient who underwent endovascular therapy to treat both infarctions.…”
Section: Introductionmentioning
confidence: 99%